Study on heavy metal contamination distribution at active landfill at different depth and radius - Mohd Latiff, Nur Hanie; Othman, Rashidi; Hj. Baharuddin, Zainul Mukrim (2018)
Malaysia is a South East Asia country where the landfill is important and where the standard of waste management needs to be improved. Landfilling is more preferable compared to another disposal method due to low cost, availability of land and environmentally friendly method of waste disposal. Even though landfilling is dominant in Malaysia, most are better known as dump sites. Other than solid waste, the percolation of water into the landfill leads to leachate formation. The migration of waste in leachate form may accelerate the heavy metal leaching. Heavy metal contamination of soil is one of major concern in landfilling. This study aims to characterize soil samples from 5 sites of active landfill in Selangor; Sungai Kertas inert waste, Kuang inert waste, Dengkil inert waste, Tanjung Dua Belas sanitary landfill and Jeram sanitary landfill to study their heavy metal contamination in the landfill environment. The soil samples were obtained at different radius; 5 to 10 m, 10 to 15 m and 15 to 20 m radius and at different depths from 0 to 30 cm, 30 to 60 cm and 60 to 90 cm deep to find the possibility of heavy metal migration from the waste cell into the deeper layers. 10 analytes were measured from soil samples using inductively coupled plasma mass spectrometry (ICP-MS). Al and Fe displayed high concentration at most of the sites with different volume of concentration at different depth and radius. Most of the sites consistently showed high contamination in deeper soil than the upper layer of the soil. The analysis of variance showed highly significant differences (P<0.0001) for all sites at different depth and radius. Even though only certain metals were highly significant but a proper remediation or precautionary measure need to be aware in order to prevent risks to human and the environment.